A History of Popular Culture in Japan : From the Seventeenth Century to the Present - Atkins, E. Taylor (Everett Taylor), 1967- (London ; New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"The first historical overview of popular culture in Japan from its origins in the 17th century to the present day, exploring themes of conflict, power, identity, and meaning in Japanese history"--Provided by publisher.
"The phenomenon of 'Cool Japan' is one of the distinctive features of global popular culture of the millennial age; people of all ages throughout the world consume and emulate cultural products made in Japan. A History of Popular Culture in Japan provides the first historical and analytical overview of popular culture in Japan from its origins in the 17th century to the present day, using it to explore broader themes of conflict, power, identity and meaning in Japanese history. E. Taylor Atkins shows how Japan is one of the earliest sites for the development of mass-produced, market-oriented cultural products consumed by urban middle and working classes. The best-known traditional arts and culture of Japan--Noh theater, monochrome ink painting, court literature, poetry and indigenous music--inhabited a world distinct from that of urban commoners, who fashioned their own expressive forms and laid the groundwork for today's 'gross national cool.' Popular culture was pivotal in the rise of Japanese nationalism, imperialism, militarism, postwar democracy, and economic development. Eschewing a chronological narrative to instead offer historiographical and analytical frameworks for understanding its subject, A History of Popular Culture in Japan synthesizes the latest scholarship from a variety of disciplines. It is a vital resource for students of Japanese cultural history wishing to gain a deeper understanding of Japan's contributions to global cultural heritage, and a nuanced view of how popular culture provides a space for Japanese to understand themselves and their place in the world"--Provided by publisher.
1. The Worst to be Said and Thought? : Defining, Debating, and Deconstructing Popular Culture -- 2. Floating Worlds : Urban Commoners and the Birth of Popular Culture in Japan -- 3. Revolt of the Chonin? : On the Radical Potential of Edo-Period Popular Culture -- 4. Popular Culture as Subject and Object of Meiji Modernization -- 5. Modernism as Modanizumu : Cultures of Cosmopolitanism in Imperial Japan -- 6. Entertaining an Empire : Popular Culture as Agent of Imperialism -- 7. "Our Spirit Against Their Steel" : Mobilizing Culture for War -- 8. Baseball, Boogie-Woogie, and Kissing Films : Democratizing Japan through Popular Culture -- 9. Monstrosity and Nostalgia in an Age of Pensive Prosperity -- 10. As GNP Falls, GNC Grows : Millennial Japan as Dream Factory -- Afterword: Contemplating Cool.
Includes bibliographical references and index.
Keywords: Popular culture -- Japan -- History; Popular culture -- Political aspects -- Japan -- History; HISTORY / Asia / Japan; HISTORY / Modern / General; HISTORY / Social History; Japan -- Civilization; Japan -- Intellectual life; Japan -- Social life and customs